The Effect Of Debt Policy On Company Value In Manufacturing Companies On The Indonesia Stock Exchange - Nurmala, Anita; Reni, Reni; Agustina, Rina; Kandias, Rhakean; Suhartini, Shanti (SINTESA, 2025)
The value of a company can be understood as market value. This is because when the stock price of a company rises, the market value can maximally provide prosperity to shareholders. High debt usage can also lower the value of the company due to the potential emergence of bankruptcy costs and agency costs. The aim of this research is to test the consistency of previous research findings and analyze the impact of debt policy on company value. The number of samples used is 15 companies, using a non-probability sampling method, specifically purposive sampling technique. The analysis technique employed is the Interaction Test or Moderated Regression Analysis (MRA). Overall, the results indicate that the DER variable does not have a significant effect on PBV. If the debt policy decreases by one unit, it results in a decrease in company value.